INTEGRITY OF VILLAGE APPARATUS IN REALIZING EXCELLENT SERVICE QUALITY IN VILLAGE KAMBULA-BULANA BUTON REGENCY - Nurhidayat, Aldi; Mahyudin, Mahyudin; Asiri, La (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2024)
The purpose of the research is to find out how the integrity of the Kambula-Bulan Village apparatus and what factors are inhibiting and supporting the integrity of the Kambula-Bulan Village apparatus of Buton Regency. The research uses a qualitative descriptive method, with data collection techniques through interviews and documentation. The results of the research show that there are several apparatus individuals who do not care about service delivery based on the four attitudes shown, namely; honest, sincere and trustworthy attitude, transparent and consistent attitude, dignified attitude and objective attitude so that it can be said that the Kambula-Bulana Village apparatus of Buton Regencylack of integrity. Negative factors that hinder an apparatus from providing integrity and professional service. Meanwhile, the positive factor that supports the apparatus in providing services with integrity is none other than the awareness of the apparatus towards their duties and responsibilities, the awareness of serving the community and the support of fellow colleagues.